Perception of EFL Students on the Use of Indonesian Language in English Class - Ivan Elian; Lailatul Musyarofah; Henry Rio Putranto (JELITA, 2023)
It has long been contentious to use Indonesian as a teaching and learning language for English classes. This research tried to investigate how the lecturer uses Indonesian in the English-language classroom. A mixed method combining quantitative and qualitative methods was used. The participants were 24 first-year students of the English Education major from STKIP PGRI Sidoarjo, class 2020A. This was a survey research. Participants were given a questionnaire with 15 questions to collect primary data. The research found that students perceived the lecturer’s use of Indonesian in the online EFL class was beneficial. Indonesian was used by lecturer to explain new vocabulary and English grammar. Related to students’ feelings, they felt more comfortable and had better understanding when the lecturer used Indonesian, especially when it was related to the material explanation. However, the advantages and disadvantages of the lecturer’s use of Indonesian in the classroom were also acknowledged by students. The findings of this research indicate that students majoring in English education still consider the use of Indonesian by lecturers having an important role in English classes.